Prevalence and Clinical Patterns of Polycystic Ovary Syndrome among Attending Babylon Reproductive-Age Educational Women Hospital for Gynecology and Pediatrics, Iraq - Intisar Hussein Hadi; Ibtisam Mohamed Saed Diekan; Ahmed Kadhim Mohammed (American Journal of Biomedicine and Pharmacy, 2026)
Background: Polycystic Ovary Syndrome (PCOS) is the most prevalent endocrine disorder affecting women of reproductive age, yet robust epidemiological data from Iraq remain sparse. Babylon Governorate, a densely populated central Iraqi province, has not previously been the subject of a dedicated hospital-based PCOS prevalence study. Objectives: To determine the prevalence of PCOS and to characterize its clinical, hormonal, and sonographic patterns among reproductive-age women attending Babylon Educational Hospital for Gynecology and Pediatrics, Hilla, Iraq. Methods: A cross-sectional descriptive study was conducted between January 2025 and December 2025. A total of 450 women aged 18–45 years attending the outpatient gynecology clinic were enrolled using a systematic random sampling approach. Diagnosis of PCOS was established according to the revised Rotterdam criteria (2003), which require at least two of the following three features: oligo-ovulation or anovulation, clinical or biochemical hyperandrogenism, and polycystic ovarian morphology on pelvic ultrasound. Standardised clinical assessment, hormonal profile, fasting glucose and insulin, lipid panel, and transvaginal or transabdominal pelvic ultrasound were performed for all participants. Results: PCOS was diagnosed in 82 out of 450 women, yielding a prevalence of 18.2% (95% CI: 14.8%–22.1%). The mean age at diagnosis was 24.7 ± 5.3 years. The most prevalent diagnostic subtype was subtype B (oligo/anovulation + polycystic ovarian morphology, no biochemical hyperandrogenism) observed in 34.1% of PCOS cases, followed by subtype A (all three criteria) in 29.3%. Oligomenorrhea was the dominant menstrual complaint (73.2%). Clinical hyperandrogenism, manifested as hirsutism, acne, or androgenic alopecia, was present in 58.5% of PCOS women. Insulin resistance, defined by a HOMA-IR ≥2.5, was detected in 56.1% of diagnosed cases. Dyslipidaemia was identified in 48.8%, and the prevalence of metabolic syndrome among PCOS women was 24.4%. Conclusions: PCOS is highly prevalent among reproductive-age women in Babylon Governorate, with a hospital-based prevalence exceeding estimates reported for the general Iraqi population. The high burden of metabolic comorbidities underscores the urgent need for integrated screening, early diagnosis, and multidisciplinary management protocols within Iraqi healthcare settings.